Developing a functional index to dynamically examine the spatio-temporal disparities of China's inclusive green growth. (June 2022) - Wang, Deqing; Hou, Yiwen; Li, Xuemei; Xu, Yan
Highlights: Propose a framework to conceptualize the inclusive green growth in China (IGGC). Construct a functional inclusive green growth index ( IGGI ( t )) with dynamic weighting to measure the continuous process of IGGC. Spatio-temporal disparities in the absolute level, velocity and acceleration of IGGC are examined. Overall and structural inequalities of IGGC are continuously decomposed. Abstract: Inclusive green growth strategy has become a worldwide consensus on sustainable development for its highlight on the coordination between social equity, economic growth quality, and environmental stability. In-depth understanding of the temporal disparity in inclusive green growth is vital for developing countries with regional imbalances to devise scientific and sustainable development strategies. Motivated by the need for continuously monitoring the time-varying process of inclusive green growth and to overcome the shortfalls of conventional inclusive green growth index in dynamic assessment, we developed a functional inclusive green growth index ( IGGI ( t )) in the context of continuous curves. The inclusive green growth in China comprises four functional sub-indices and is built upon four pillars, namely the economic development, social opportunity equity, sustainable production and consumption, and eco-environmental protection. All normalized indicators within each pillar are individually smoothed into dynamically evolving curves, and then are objectively aggregated using the functional Shannon's entropy weights. Applying the IGGI ( t ) to examine disparities in China's provincial inclusive green growth from 2000 to 2019 demonstrates significant disparity in the absolute level of inclusive green growth among the three regions in China, whereas disparities in the velocity and acceleration of regional inclusive green growth are not significant. Furthermore, the overall and structural inequality of China's inclusive green growth was decomposed via the extended functional Dagum index and targeted policies for reducing regional inequality and improving China's overall inclusive green growth are proposed based on discussions of empirical results. Finally, a sensitivity analysis was conducted to verify the robustness of conclusions derived from using the IGGI ( t ). We contributed to proposing a dynamic framework for evaluating the quality of green growth and providing a reference for developing countries, including China, to coordinate economic development, social inclusiveness, and eco-environmental protection.